Financial Systems and Economic Growth: An Evaluation Framework for Policy - Iris Claus; Veronica Jacobsen; Brock Jera (New Zealand Government, The Treasury, 2004)
The purpose of this paper is to develop an analytical framework for discussing the link between financial systems and economic growth. Financial systems help overcome an information asymmetry between borrowers and lenders. If they do not function well, economic growth will be negatively affected. Three policy implications follow. First, the analysis underscores the importance of maintaining solid legal foundations because the financial system relies on these. Second, it demonstrates the necessity for reforming tax policy as it applies to investment, as this is demonstrated to significantly affect the operation of the financial system. Finally, given the importance of financial development for economic growth, a more in-depth review of New Zealand's financial system in the context of financial regulation and supervision would be valuable.
Keywords: G10; G20; G38; H25; K20; K34; O16; 330; Economic growth; financial development; financial systems; financial regulation; legal system; institutions; tax